Pusat Seni Musik Perkusi Tradisional Rokan Hulu Di Pasir Pengaraian Dengan Pendekatan Arsitektur Neo-Vernakular - Wahyu Dwi Syaputra; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Traditional music in Malay tradition is used as a means or media of ceremonial cultural ceremonies (ritual), accompaniment dance, media entertainment, media communication, media self-expression. Rokan Hulu has a variety of traditional percussion music in the form of Gondang, Oguong, Gong, Calompong, Gambus. As time goes by, the community's interest in traditional music art is very low, especially for the younger generation and the absence of a container to study and preserve traditional percussion music. Therefore, this study aims to design a percussion music art Center for the development and preservation of percussion music potential to be able to improve the public knowledge about traditional percussion music. The selection of Rokan Hulu Regency is a central location for traditional percussion music because it has good potential, strategic location, the art heritage of music. The method used in this design is to use the Neo-vernacular architecture approach by applying the principles and design ideas that exist in the architectural characteristics of Rokan IV Koto with the addition of modern elements inside . The concept used is the concept of the Untaian Borogong transformation, which is expected to unite between architecture and music art. The final result is the design of a traditional percussion music art Center presenting the local music art of Rokan Hulu.Keyword: Architecture Neo Vernacular, Rokan Hulu, Culture, Culture Center